Elementary Information Security - Smith Richard E (Jones And Bartlett Learning, 2013)
This book covers the complete breadth of essential topics within information security. Preface, Security from the Ground Up, Controlling a Computer, Controlling Files, Sharing Files, Storing Files, Authenticating People, Encrypting Files, Secret and Public Keys, Encrypting Volumes, Connecting Computers, Networks of Networks, End-to-End Networking, Network Encryption, Internet Services and Email, The World Wide Web, Governments and Secrecy, Acronyms, Alternative Security Terms and Concepts, Index, Credits.